Analisis Perhitungan, Pemotongan, Penyetoran dan Pelaporan Pajak Penghasilan (PPh) Pasal 21 Atas Penerima Pensiun pada PT Taspen (Persero) Cabang Surakarta - Fauzan Arif Siraj (Neolectura, 2021)
Income Tax is a tax levied on the object of tax on his income. Income tax will always be imposed on people or business entities earning income in Indonesia. The tax applicable to employees and pension recipients is Income Tax Article 21. The subject of Article 21 of the Act in particular concerning pensions and Article 21 in particular about pensions is pensions themselves. Therefore, participants who receive pension contributions are Taxpayers PPh Article 21. This study aims to find out the calculation, deduction, deposit and reporting of Income Tax Article 21 at PT Taspen (Persero) Surakarta Branch whether it is in accordance with Law No. 36 of 2008 and the Law on penile funds. The object of this research was taken at PT Taspen (Persero) Surakarta Branch. The research method used is descriptive analysis method. The results of the research obtained are the mechanism of Income Tax article 21 on periodic pension recipients at PT Taspen (Persero) Surakarta Branch in accordance with Law No. 36 of 2008 and Regulation of the Director General of Taxation No. PER-16/PJ/2016. The tax calculation for pension recipients is still three people who are not suitable.